KONTRIBUSI LIMBAH DETERJEN TERHADAP STATUS KEHIDUPAN PERAIRAN DI DAS CITARUM HULU - Wage Komarawidjaja (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2004)
Soap is defined as compound of fats, fatty acids and caustics soda. Thesecompounds work to reduce surface tension and increase its cleansing ability. The term “detergent” usually refer to synthetics compounds, but has broader ability, not only reducing surface tension and increasing its cleansing ability but also has softening and emulsifying ability.Unfortunately, detergent in certain concentration can harm to aquatic organism such as plankton, mussel, mollusk and fish. In bioassays test, high detergent concentrations induced mortality in gill cells and reduced filtration rate of the mussel. In some report cited said that concentrations above 0.2 mg/L of anionic detergent already elicited detrimental, and sub-lethal effects in all test organisms.Therefore, in upper Citarum Catchments Area which has detergent concentration significantly above 0.2 mg/L could harm to sessile invertebrate organisms. And in the long period it may influence the diver and abundance of aquatic organisms.